Bridgehead vicinal diallylation of norbornene derivatives and extension to propellane derivatives via ring-closing metathesis - Kotha, Sambasivarao; Gunta, Rama (Beilstein Journal of Organic Chemistry, 2016)
Here, we report a simple synthetic strategy to the bridgehead vicinal diallylation of norbornene derivatives. These substrates are useful to generate propellanes via ring-closing metathesis. Single-crystal X-ray diffraction analysis of four compounds led to the realization of configurational correction of earlier reported molecules.
Keywords: norbornene; propellane derivatives; ring-closing metathesis; single-crystal X-ray diffraction; vicinal diallylation

(untitled) - Ghosh, S.; Banerjee, S. (ARKIVOC, 2002)

(untitled) - Thansandote, P.; Hulcoop, D. G.; Langer, M.; Lautens, M. (J. Org. Chem., 2009)

(untitled) - Parham, M. E.; Frazer, M. G.; Bradsher, C. K. (J. Org. Chem., 1972)

(untitled) - Engler, E. M.; Andose, J. D.; Schleyer, P. V. R. (J. Am. Chem. Soc., 1973)

Ring Opening Metathesis Polymerisation and Related Chemistry: State of the Art and Visions for the New Century - North, M. (ROMP of Norbornene Derivatives of Amino Esters and Amino Acids, 2002)

(untitled) - Eddolls, J. P.; Iqbal, M.; Roberts, S. M.; Santoro, M. G. (Tetrahedron, 2004)

(untitled) - Grieco, P. A.; Abood, N. (J. Org. Chem., 1989)

(untitled) - Kotha, S.; Banerjee, S. (RSC Adv., 2013)

(untitled) - Wu, H.-J.; Tsai, S.-H.; Chern, J.-H.; Lin, H.-C. (J. Org. Chem., 1997)

(untitled) - Masusai, C.; Soorukram, D.; Kuhakarn, C.; Tuchinda, P.; Pakawatchai, C.; Saithong, S.; Reutrakul, V.; Pohmakotr, M. (J. Org. Chem., 2015)

(untitled) - Kotha, S.; Dipak, M. K. (Chem. – Eur. J., 2006)

(untitled) - Ranganathan, D.; Haridas, V.; Kurur, S.; Nagaraj, R.; Bikshapathy, E.; Kunwar, A. C.; Sarma, A. V. S.; Vairamani, M. (J. Org. Chem., 2000)

(untitled) - Holub, N.; Blechert, S. (Chem. – Asian J., 2007)

(untitled) - Kotha, S.; Meshram, M.; Khedkar, P.; Banerjee, S.; Deodhar, D. (Beilstein J. Org. Chem., 2015)

(untitled) - Malik, C. K.; Yadav, R. N.; Drew, M. G. B.; Ghosh, S. (J. Org. Chem., 2009)

(untitled) - Kotha, S.; Gunta, R. (Beilstein J. Org. Chem., 2015)

(untitled) - Kotha, S.; Ravikumar, O. (Beilstein J. Org. Chem., 2015)

(untitled) - Kotha, S.; Ravikumar, O. (Eur. J. Org. Chem., 2014)

(untitled) - Funel, J.-A.; Prunet, J. (Synlett, 2005)

(untitled) - Kiss, L.; Kardos, M.; Forró, E.; Fülöp, F. (Eur. J. Org. Chem., 2015)

(untitled) - Bose, S.; Ghosh, M.; Ghosh, S. (J. Org. Chem., 2012)

(untitled) - Zhu, H.; Ye, C.; Chen, Z. (Chin. J. Org. Chem., 2015)

(untitled) - Han, J.; Zhang, L.; Zhu, Y.; Zheng, Y.; Chen, X.; Huang, Z.-B.; Shi, D.-Q.; Zhao, Y. (Chem. Commun., 2016)

Handbook of Metathesis: Applications in Organic Synthesis - Grubbs, R. H.; O'Leary, D. J. (Wiley-VCH, 2015)

Metathesis in Natural Product Synthesis: Strategies, Substrates and Catalysts - Cossy, J.; Arseniyadis, S.; Meyer, C. (Wiley-VCH, 2010)

Olefin Metathesis: Theory and Practice - Grela, K. (John Wiley & Sons, 2014)

(untitled) - Kotha, S.; Krishna, N. G.; Halder, S.; Misra, S. (Org. Biomol. Chem., 2011)

(untitled) - Kotha, S.; Mandal, K.; Deb, A. C.; Banerjee, S. (Tetrahedron Lett., 2004)

(untitled) - Kotha, S.; Mandal, K.; Tiwari, A.; Mobin, S. M. (Chem. – Eur. J., 2006)

(untitled) - Kotha, S.; Mandal, K. (Tetrahedron Lett., 2004)

(untitled) - Prunet, J. (Eur. J. Org. Chem., 2011)

(untitled) - Ghosh, S.; Ghosh, S.; Sarkar, N. (J. Chem. Sci., 2006)

(untitled) - Keck, G. E.; Kordik, C. P. (Tetrahedron Lett., 1993)

Conjugate Addition Reactions in Organic Synthesis - Perlmutter, P. (Pergamon Press, 1992)

(untitled) - Valderrama, J. A.; Espinoza, O.; González, M. F.; Tapia, R. A.; Rodríguez, J. A.; Theoduloz, C.; Schmeda-Hirschmann, G. (Tetrahedron, 2006)

(untitled) - Patney, H. K.; Paddon-Row, M. N. (Synthesis, 1986)

(untitled) - Singh, V.; Raju, B. N. S. (Indian J. Chem., 1996)

(untitled) - Kotha, S.; Gunta, R. (Beilstein J. Org. Chem., 2015)

Olefin Metathesis: Theory and Practice - van Lierop, B. J.; Lummiss, J. A. M.; Fogg, D. E. (John Wiley & Sons, 2014)

(untitled) - Garratt, P. J.; Hollowood, F. (J. Org. Chem., 1982)

(untitled) - Kotha, S.; Gunta, R. (Tetrahedron Lett., 2016)

(untitled) - Torres, E.; Leiva, R.; Gazzarrini, S.; Rey-Carrizo, M.; Frigolé-Vivas, M.; Moroni, A.; Naesens, L.; Vázquez, S. (ACS Med. Chem. Lett., 2014)